ANALISIS PENGALAMAN KERJA DAN KOMPETENSI TERHADAP KINERJA ORGANISASI PADA USAHA KECIL JASA KONSULTAN BIDANG KONSTRUKSI - Amiruddin Siregar; Sri Indrastuti; Hamdi Agustin (Proceeding International Conference on Social Sciences, 2026)
This study aims to conduct an in-depth analysis of the role of linear work experience and competence in influencing employee performance at a supervision consulting company in Siak Regency using a qualitative literature review approach. The research was carried out through a systematic review of various scholarly sources, including accredited journals, textbooks, research reports, and policy documents relevant to the topic. The qualitative approach was employed to interpret theoretical and empirical findings contextually in order to build a comprehensive understanding of the relationships among the variables. The findings indicate that linear work experience has a positive effect on performance improvement, as the alignment between previous experience and current job roles strengthens technical abilities, decision-making accuracy, and task execution efficiency. Meanwhile, competence—which encompasses knowledge, skills, and professional attitudes—has been proven to be a key factor in driving productivity and work quality. The synergy between linear work experience and competence forms a crucial foundation for achieving optimal performance in supervision consulting firms. Conceptually, the results of this study affirm that human resource development should be directed toward enhancing the alignment of work experience with job roles and strengthening competencies through continuous training to sustainably improve organizational performance.